Multifaceted manifestations: A case report of MRSA pneumonia with sepsis, pyelonephritis, and ileus muscle abscess - Ahmad Damlakhy; Zohaib A. Khan; Anas Abdel‐Qader; Dmitrii Chernyshev; Emily Ross (Clinical Case Reports, 2024)
Key Clinical Message Methicillin‐resistant staph aureus (MRSA) infections are challenging to treat, and with the emergence of community‐associated MRSA (CA‐MRSA) strains, early consideration of this pathogen in populations without typical risk factors is critical. Here we present a case of CA‐MRSA pneumonia that resulted in Community‐acquired pneumonia (CAP) with septic shock, pyelonephritis, and muscle abscess.